Managing family dynamics and how upbringing affects relationships in adulthood - Adaobi Jennifer Iloakasia; Titik Muti'ah; Zahra Frida Intani (LP2M Universitas Sarjanawiyata Tamansiswa, 2025)
Early family dynamics and upbringing play a vital role in shaping adult relationship patterns. Childhood experiences—such as emotional climate, communication styles, and parental interactions—can significantly influence how individuals develop trust, manage emotions, and resolve conflicts later in life. This study employed a descriptive survey design to examine how these early influences affect adult relationships among 101 participants aged 18 and above in Anambra State, Nigeria. A stratified random sampling method ensured representation across age and gender. Data were collected through the validated Family Dynamics and Adult Relationship Patterns Scale (FDARPS), using a 4-point Likert scale (Cronbach’s Alpha = 0.77). Findings revealed that parenting style (M = 3.02), sibling relationships (M = 2.65), and childhood attachment (M = 2.52) significantly shaped adult interpersonal styles, while early interactions and family stability had less impact. Positive upbringing elements—such as parental support (M = 2.97), role models (M = 2.87), and early encouragement (M = 2.88)—fostered healthy relationships, whereas open communication (M = 1.77) was less influential. Common adaptive strategies among those with dysfunctional family backgrounds included mindfulness (M = 3.08), support groups (M = 3.06), and therapy (M = 3.01). ANOVA results indicated significant effects of age and age-gender interactions, but not gender alone. The study concludes that early family experiences significantly shape adult relational outcomes. It recommends that families, educators, and counselors emphasize emotional support, healthy communication, and positive role modeling to nurture stronger future relationships.